Consumer acceptance of cysteine-enhanced yogurt - Bala, Soumya; Schmidt, Karen A. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2014)
Within cells, cysteine can be synthesized from methionine by the enzyme γ-cystathionase. Cysteine is then utilized to synthesize glutathione, which has many functions in cells that contribute to good health. Certain subpopulations, however, especially the elderly, have decreased γ-cystathionase activity. Thus, dietary cysteine may be beneficial in maintaining health. In previous reports, a yogurt with enhanced cysteine content was made by incorporating whey protein isolate (WPI) into the mix’s dairy base combined with a process treatment to minimize cysteine denaturation. The gel quality of this yogurt matched or exceeded that of a yogurt that was formulated and processed to mimic an industrially manufactured product. More importantly, the cysteine content was 3 times greater, and the gel quality was stable throughout a 60-day shelf life. With this evidence, the question remained whether the flavor of an enhanced cysteine yogurt would be acceptable. Because addition of whey-based products in yogurt has been reported to affect flavor and texture properties, this study was undertaken to determine consumer liking of a high-cysteine yogurt. Formulas were adjusted to contain sugar and vanillin, and these mixes were processed to produce high-cysteine and low-cysteine yogurts. Yogurts were stored at 4°C for 1 week, then evaluated by a group of 119 consumers. Consumers rated yogurts based on their liking of appearance, thickness, flavor, aftertaste, and overall acceptability using a 9-point hedonic scale ranging from dislike extremely (1) to like extremely (9). Overall, consumers rated the high- and low-cysteine yogurts similarly for flavor (6.1), aftertaste (6.1), and overall acceptability (6.3), with mean scores corresponding to “like slightly” to “like moderately.” Consumers liked the thickness of the high-cysteine yogurt more than the low-cysteine yogurt but liked the appearance of the low-cysteine yogurt more than the high-cysteine yogurt. The high-cysteine yogurt had approximately 3 times more cysteine than the low-cysteine yogurt. These results indicate that a high-cysteine yogurt may be a useful and acceptable food system to provide dietary cysteine.
Dairy Research, 2013 is known as Dairy Day, 2013
Keywords: Yogurt; Cysteine; Consumer preference